Brownfield regeneration and the shifting of financial risk: between plans and reality in public-private partnerships - van den Hurk, Martijn; Williams, David; Luis dos Santos Pereira, Alvaro; Tallon, Andrew (Urban research & practice, 2024)
Internationally, brownfield regeneration projects are delivered through public-private partnerships that form complex legal and structural delivery mechanisms. Utilizing private-sector finance and skills is an accepted practice to reduce financial risk for the public sector while delivering profits for the private sector. This article explores three international brownfield regeneration schemes. It highlights how and why financial risk remains within the public sector from the outset or returns to the public sector over time, despite the initial rhetoric for this burden to be carried mainly by the private sector. The analysis improves the empirical understanding of financial risk dynamics in brownfield regeneration.